PEMANFAATAN BOT UNTUK OTOMATISASI LAYANAN HELPDESK AKADEMIK MAHASISWA - Hanna Hilyati Aulia; Rahmah Ningsih; Ayyesha Dara Fayola; Dede Mercy Rolando (Media Inovasi Pendidikan dan Publikasi, 2023)
IAIN Metro as an educational institution is also required to be able to improve community service performance. Online helpdesk services have developed for service satisfaction and digitization of the bureaucracy. However, from this rapid development, new problems emerged, namely admin limitations, service time in handling and the absence of an online service system structure. This service aims to improve service quality through the use of telegram bots as a forum for message automation and an integrated service system. The method used is ADDIE (analysis, design, development, implementation and evaluation). This activity is able to increase the integrity zone of IAIN Metro in terms of public services with the automation of the student academic helpdesk service system. Based on the evaluation results, this academic helpdesk service bot can increase student satisfaction in terms of response speed, ease of use, interaction quality and interaction quality with a good score.